The Internationalisation of Public Welfare Policy - Banks, J.; Disney, R.; Duncan, Alan; Van Reenan, J. (Wiley on Line, 2005)
With increasing globalisation of knowledge, there are increased opportunities to ‘learn’ from the experience of policy interventions elsewhere. This paper presents evidence on the extent of international convergence in public policy, with particular focus on labour, welfare, savings and retirement policy. Questions addressed in this framework include: to what extent is policy diffusion or convergence a real and relevant phenomenon? What role have economists played in the transfer of policy across national domains? Has policy transfer led to ‘better’ public policy? Are there any practical limitations to policy convergence?